Novel mobility test to assess functional vision in patients with inherited retinal dystrophies - Daniel C. Chung; Sarah McCague; Zi‐Fan Yu; Satha Thill; Julie DiStefano‐Pappas; Jean Bennett; Dominique Cross; Kathleen Marshall; Jennifer Wellman; Katherine A. High (2017)
This novel endpoint tracks functional vision changes in patients with inherited retinal dystrophies (IRDs) over time.The aims of the study were to determine whether a multi-luminance mobility test (MLMT) can detect functional vision changes over time in subjects with IRDs and to assess natural history and potential effects of investigational agents.This is a prospective, observational study.Sixty-two subjects were enrolled. Sixty (29 normal sighted and 31 visually impaired) were eligible; 54 (28 visually impaired and 26 normal-sighted) completed all testing visits.Subjects navigated MLMT courses three times over 1 year. At each visit, subjects completed testing using individual eyes, and both eyes, at up to nine standardized, increasing luminance levels (range 1 to 400 lux). Accuracy and speed were evaluated and compared with visual acuity (VA), visual field (VF) and a visual function questionnaire.Accuracy and speed of normal and visually impaired subjects on MLMT, and reliability and content validity of MLMT were the main outcome measures.MLMT distinguished normal-sighted from visually impaired subjects. All control subjects passed all MLMT attempts at all tested light levels. Visually impaired subjects' performance varied widely; some declined over 1 year. Performance declined markedly below certain VA and VF thresholds. Concordance on performance on two baseline visits was high: correlations for accuracy were 94% and 98% for lowest common and highest common lux levels.MLMT differentiated visually impaired from control populations and, in visually impaired subjects, identified a range of performances; and tracked performance declines over time, consistent with these progressive conditions.